Fatima's Great Outdoors - Tariq, Ambreen; Lewis, Stevie (New York : Kokila, 2021)
An immigrant family embarks on their first camping trip in the Midwest.
Keywords: Immigrants -- Juvenile fiction; Camping -- Juvenile fiction; Immigrants -- Fiction; Camping -- Fiction